Cansolv® SO2 Scrubbing System: Review Of Commercial Applications For Smelter SO2 Emissions Control - Valérie Léveillé (The Southern African Institute of Mining and Metallurgy, 2009)
As new legislation drives to lower SO2 emissions from metallurgical plants, plant managers face the challenge of keeping their costs under control. The Cansolv® SO2 Scrubbing System has been broadly adopted in the non-ferrous industry as a cost effective solution for smelter operators to meet the new SO2 emissions targets. The Cansolv® SO2 Scrubbing System is an amine-based regenerable process that selectively absorbs SO2 from a variety of gases, including dilute smelter gases, such as furnace and converter gases. The system produces a pure, water-saturated SO2 byproduct stream, which can then be directed to the front end of a sulfuric acid plant for conversion to sulfuric acid. When deployed in a smelter complex, the Cansolv® SO2 Scrubbing System may also be used to process acid plant tail gas, allowing single absorption sulfuric acid plants to achieve emissions an order of magnitude lower than that of a double absorption acid plant with a lower capital investment. Depending on inlet gas temperature SO2 emissions in the treated gas can be controlled to as low as 55 mg/Nm3. This paper will describe some of the applications where customers have or are planning to use the Cansolv® SO2 Scrubbing System and what as well as which features and cost advantages for the treatment of smelter gases were key to the technology choice.